1972
DOI: 10.1111/j.1365-2362.1972.tb00575.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Lipids and Steroid Hormones in Patients with Hypercholesterolaemia or Hyperlipaemia during Dehydroepiandrosterone Sulphate Administration*

Abstract: DHEA sulphste was administered orally in doses of 20 to 80 mg to 13 subjects with hypercholesterolaemia or hyperlipaemia. Plasma lipid and neutral steroid eulphate levels aa well as the excretion of individual ll-deoxy-17-ketosteroids and estrogens in urine were investigated before and during the treatment. No effect was observed on plasma free or esterified cholesterol, on total or individual phospholipid values. or on routine blood haematological or chemical analyses. However, the plasma CIp steroid sulphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1976
1976
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…46 In addition, the 24-hour urinary DHEA-S levels were inversely related to blood cholesterol concentrations in industrial workers. 48 DHEA feeding to humans resulted in no change in serum cholesterol in one study 47 but was associated with decreased LDL cholesterol levels in another study. 6 While all of the above-noted associations support the epidemiological data indicating that DHEA-S levels were inversely correlated to subsequent death from atherosclerosis in humans, 8 the one published study of DHEA levels in patients undergoing coronary angiography did not demonstrate differences in plasma DHEA concentrations between patients with positive and those with negative angiograms.…”
Section: Arteriosclerosis Voi 9 No 2 March/april 1989mentioning
confidence: 94%
“…46 In addition, the 24-hour urinary DHEA-S levels were inversely related to blood cholesterol concentrations in industrial workers. 48 DHEA feeding to humans resulted in no change in serum cholesterol in one study 47 but was associated with decreased LDL cholesterol levels in another study. 6 While all of the above-noted associations support the epidemiological data indicating that DHEA-S levels were inversely correlated to subsequent death from atherosclerosis in humans, 8 the one published study of DHEA levels in patients undergoing coronary angiography did not demonstrate differences in plasma DHEA concentrations between patients with positive and those with negative angiograms.…”
Section: Arteriosclerosis Voi 9 No 2 March/april 1989mentioning
confidence: 94%
“…The beneficial effect on lipids, consisting of the prevention of hypercholesterolemia in rats made hypothyroid with PTU, could account for the inverse correlation between DHEA and death from cardiovascular disease documented in men ( Barrett-Connor, Khaw and Yen 1986). Indeed DHEA-S administration in men has been shown to induce a decrease of LDL-Chol levels (Adlercreutz, Kerstell, Schaumann, Svanborg and Vihko 1972;Nestler, Barlascini, Clore and Backard 1988); however in this latter study a decrease of HDL-Chol was found too, although not significant, and no change was documented for LDL-Chol/HDL-Chol ratio. In addition, a striking inverse correlation between DHEA-S and LDL-Chol levels in human fetal (Parker, Simpson, Bilheimer, Leveno, Carr and MacDonald 1980) as well as adult serum (Nafziger, Jenkins, Bowlin and Pearson 1990) has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…50 Administration of 40 to 80 mg of oral DHEA-S for several weeks did not change lipoproteins. 51 The question of whether or not more physiologic replacement alters lipoprotein profiles has been addressed preliminarily, in a placebo-controlled fashion, by both Morales et al 24 and our group. 23 Both studies observed lipoprotein changes induced with 50 mg/d of DHEA in either older men and women for 3 months or women alone for 3 weeks, and demonstrated either a slight decrease in HDL or a decrease in fasting triglycerides.…”
Section: Serum Lipidsmentioning
confidence: 99%